Franklin Delano Roosevelt: A Famous Patient - Hart, Curtis W. (Journal of religion and health, 2014)
Franklin Delano Roosevelt is arguably one of the greatest of American Presidents. His encounter with the polio that crippled him at an early age and its transformative impact upon him are here discussed with particular reference to his relationship with his physician, Dr. George Draper. This transformation liberated energy in Roosevelt to lead and to show empathy for others in ways that both challenged the political and social status quo in the USA as well as helped save the world from the threat of Fascism in World War II. This essay seeks to demonstrate how an investigation of the life and struggles of this famous patient is one avenue for relating the study of the humanities to medical education. An earlier version of this paper was presented as the Heberden Lecture in the History of Medicine at the New York Academy of Medicine in 2012.